The role of self-stigma in mediating the association between externalizing and treatment-seeking intention - Davis, Brianna N.; Drislane, Laura E. (Frontiers in Psychology, 2025)
IntroductionSelf-stigma occurs when an individual internalizes and accepts the stereotypes and negative views of mental illness endorsed by the public. High levels of self-stigma negatively predict treatment-seeking intention, but little work has examined how self-stigma functions specifically among individuals with tendencies toward impulsivity.MethodsThe current study implemented structural equation modeling (SEM) to investigate whether self-stigma as operationalized by the MHSIS model mediated the relationship between externalizing proneness and the intention to seek mental health treatment. Data were collected from community participants (N = 394) preselected for the presence of impulse control problems (e.g., ADHD, alcohol use) and mental health concerns.ResultsExternalizing was weakly negatively associated with the intention to seek treatment. Externalizing proneness was associated with higher levels of self-stigma, particularly at the later stages (i.e., application); however, self-stigma did not appear to mediate the association between externalizing and reduced treatment seeking intention.DiscussionThis study informs how self-stigma exists across the externalizing spectrum and may serve as a transdiagnostic target for intervention.